Reproduction and Robustness of Kao et al. (2024): "Female Representation and Legitimacy". A Report from the 2024 UC Berkeley Replication Games - Thomas Brailey; Edmund Kelly; Angela Odermatt; Albert Ward (Institute for Replication (I4R), 2024)
Kao et al. (2024) use phone-based survey experiments in Jordan, Tunisia and Morocco to test whether established theories about the effect of descriptive representation on perceived democratic legitimacy hold in the Middle East. They find that the presence of women in deliberative bodies legitimizes decision-making even in more socially conservative, less democratic societies. We blindly reproduced their study, and then extend their analysis with five additional robustness checks. We find that their analysis is reproducible and robust in several ways, although there were ambiguities in the original text which prolonged this process. Finally, we also extended their analysis by using iterative machine learning models to study heterogeneous treatment effects. We find that marital status as well as pre-treatment attitudes on related issues affect the response to the treatment.
Keywords: 330